EVALUATION OF APPROACHES OF NURSING STUDENTS TO OCCUPATIONAL HEALTH AND SAFETY - Karaçuha, Melek Ersoy; Uslu, Ayşenur (Acta Scientiae et Intellectus, 2024)
This research was carried out to evaluate the approach to the occupational health and safety of nursing students who are educated at Department of Nursing - Sinop University School of Health. The research which is descriptive was carried out between May-June 2016 with 304 nursing students who accepted to participate to the research. The research data was obtained from a questionnaire with totally 25 questions prepared by the researchers, including questions about socio-demographic characteristics, questions about legislation related to occupational health and safety, questions about occupational health and safety related professional approaches. In the findings of this research, it was found that the relationship between the classes in which the nursing students are being educated and given answers to some questions which evaluate occupational and legislative approaches to occupational health and safety is significant (p <0.05) and according to the ANOVA test, the difference between these questions and the classes is significant (p <0.05) and according to Tamhane’s T2 test, it was determined that this difference increase according to class grade. As a result of this research, it has been determined that nursing students have very knowledgeable, positive and gratifying approaches intended for protecting the health of themselves and patients / healthy individuals in terms of occupational health and safety. In addition, due to the risks related to occupational health and safety that may be encountered in working conditions, in order to draw their attention and reinforce their knowledge it may be suggested to place occupational health and safety related courses into their curriculum.